Evaluation of sodium diclofenac release using natural rubber latex as carrier - Aielo, Patricia B. [UNESP]; Borges, Felipe A. [UNESP]; Romeira, Karoline M. [UNESP]; Miranda, Matheus Carlos Romeiro [UNESP]; Arruda, Larisa B. De [UNESP]; L. Filho, Paulo Noronha [UNESP]; Drago, Bruno De C. [UNESP]; Herculano, Rondinelli Donizetti [UNESP] (ABM, ABC, ABPol, 2014)
Sodium Diclofenac is a non-steroidal anti-inflammatory drug (NSAID) taken to reduce inflammation and, as an analgesic, reduce pain. Although this drug is widely used in the general population, properties such as the short half-time and some side effects restrict its clinical use. The most common side effects are: gastric irritation, gastritis, peptic ulcer and bleeding. Studies involving biomaterials as carrier for drug release have been proving their efficiency in overcoming those problems and better controling the release rate and targeting of the drug. Natural rubber latex (NRL) has been proven excellent for its biocompatibility and ability to stimulate angiogenesis, cellular adhesion and the formation of extracellular matrix, promoting the replacement and regeneration of tissue. In this work, a NRL membrane is used to deliver sodium diclofenac. Sodium diclofenac (NaDic) was found to be adsorbed on the NRL membrane, with little or no incorporation into the membrane bulk, according to energy dispersive Scanning Electron Microscopy with X-Ray microanalysis (SEM-EDS) spectroscopy. In addition, FT-IR shows that there is no molecular-level interaction between drug and NRL. Already, the X-Ray Diffraction (XRD) of NaDic-NRL shows a broader one spectrum than the sharper halo (amorphous characteristic XRD spectrum) of pure NRL. More importantly, the release time of diclofenac in a NRL membrane in vitro was increased from the typical 2-3 h for oral tablets to ca. 74 h. The kinetics of the drug release could be fitted with a double exponential function, with two characteristic times of 0.899 and 32.102 h. In this study, we demonstrated that the interesting properties provided by NRL membranes combined with a controlled release of drug is relevant for biomedical applications.
Keywords: Membranes; Natural rubber; Sodium diclofenac; Drug delivery system; Biomaterials